Sosiologi Masyarakat Selayar - Mr. Ahmadin (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2022)
The Selayar Community is a term for residents who live in the administrative area of ​​the Selayar Islands Regency, South Sulawesi Province of Indonesia. The people who live in the southernmost district of Sulawesi Island are often considered to be speakers of the Konjo dialect of the Makassar language or also called the Selayar tribe. Is the social system of the Selayar people trying to get out of the shadow of their parent ethnicity (Makassar)? This question is indeed important to answer, but what is certain is that the culture of the Selayar people is the formation of various immigrant cultural influences. Using a historical sociology approach, this paper discusses the social interactions of the Selayar people, social strata, social groups, power and authority, social changes, and social deviations. The study of the Selayar people in this sociological view will at least provide an understanding of social characteristics and cultural heritage by looking at the synchronicity between the past and present reality.